Manajemen Pemeliharaan Peralatan Berbasis Web - Rasyidah; Asraf (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2023)
The Teluk Sirih Power Plant (PLTU), owned by PT. PLN (Persero) in West Sumatra, utilizes coal as its primary energy source. Located in Teluk Sirih Village, Padang City, with two units each generating 112 MW of power, routine maintenance is pivotal in maintaining the electricity production performance. Understanding work instructions, Occupational Health and Safety (K3) policies, and maintenance-related information is of paramount importance to ensure efficient maintenance practices. However, during visits and interviews, it was revealed that there are differences in understanding work instructions, K3 policies, and maintenance-related information between experienced and new employees, which can impede maintenance activities. The research titled "Design and Development of Maintenance Information System at PT. PLN (Persero) UPK PLTU Teluk Sirih" aims to address these differences. By designing a maintenance information system, employees can easily access work instructions, K3 policies, and established maintenance information within the organization. This will facilitate adaptation for new employees and updating the understanding of experienced employees regarding the latest technology and procedures. With the existence of the PLTU maintenance information system, employees can learn work instructions, K3 policies, and maintenance-related information, thereby eliminating differences in understanding. Therefore, it is expected that the efficiency and effectiveness of maintenance at the Teluk Sirih Power Plant will be enhanced, ultimately supporting optimal electricity production